EFEKTIVITAS VAGAL NERVE STIMULATION (VNS) TERHADAP DISRITMIA JANTUNG - Pius A. L. Berek (Jurnal Sahabat Keperawatan, 2020)
Dysrhythmia is a heart rate disorder that includes frequency or rhythm disorders or both. One of the nursing actions to overcome is doing Vagal Nerve Stimulation (VNS), includes emphasis on one side of carotid sinus, emphasis on periorbital sinus, and performing valsalava maneuver by coughing. This is believed to increase release of acetylcholine in heart, where the acetylcholine is captured by SA node in left atrium and serves as an inhibitor of electrical stimulation of heart. The release of acetylcholine production is expected to inhibit cardiac irritability so ventricular contraction can be reduced to a minimum. This will appear clearly in state of dysrhythmias, especially atrial fibrillation. In atrial fibrillation, the impulses produced in atrium will exceed normal state, which results in electrical conductance of heart to SA node, continued to AV node and to purkinje fibers to increase ventricular contractions in projecting blood out of heart. If the impulses produced by atrium are irregular, the same thing happens to ventricles, which is to make irregular heart contractions as well. The result is the heart does not have time to relax to give blood to coronary arteries. If not handled properly, this is very dangerous for heart. VNS action by providing stimulation to vagus nerve will greatly help overcome this problem because the ends of the vagus nerve lead to SA node and AV node. By providing stimulation to vagus nerve, the signal will be sent to efferent to release ACh. It is hoped that this ACh will inhibit impulses from SA node and AV node so the heart can contract according to the body's needs.